2022
DOI: 10.1111/papr.13165
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin—Friend or foe?

Abstract: Background Gabapentin is a recommended first‐line agent for treating neuropathic pain; however, its efficacy rate is reportedly low, and the risk of adverse events is high. A plausible explanation for this lies with its wide range of actions, the entirety of which have yet to be fully elucidated. Methods A review of the literature was conducted on gabapentin's known and proposed analgesic mechanisms of action, as well as potentially opposing or detrimental actions. Results Gabapentin's classical analgesic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
0
10
0
4
Order By: Relevance
“…The development of chronic pain is associated with multiple cellular plasticity mechanisms within the pain processing system ( 42 45 ). On the level of the ACC, changes in neuronal excitability, synaptic plasticity, and alterations in the connectivity pattern have been described that might explain the phenotype ( 19 , 21 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of chronic pain is associated with multiple cellular plasticity mechanisms within the pain processing system ( 42 45 ). On the level of the ACC, changes in neuronal excitability, synaptic plasticity, and alterations in the connectivity pattern have been described that might explain the phenotype ( 19 , 21 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The network action observed in our study seem paradoxical as increased activity in the ACC is considered as a hallmark of the chronic pain condition ( 19 23 ). It is therefore generally assumed that analgesics exert their effect by reducing neuronal activity, which has been suggested to be the mode of action of GBP in the spinal cord, periaqueductal grey and thalamus ( 42 44 ). The paradoxical increased excitability of the ACC, on the other hand, could not only activate descending modulatory pathways but also generate a rewarding signal that target mainly the affective/emotional component of pain ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…[4] In the same model, ALC also reduced microglial activation in the CNS, suggesting it may target both peripheral and central mechanisms that contribute to pain from inflammation within the nervous system. Gabapentinoid agents including gabapentin and pregabalin work through several different mechanisms, [98][99][100] but their effect has been promising in terms of ameliorating CP pain both in rat models [80,101] and human clinical studies. Pregabalin has been shown to significantly reduce pain compared to placebo in a randomized controlled trial and has even been shown to have moderate inhibitory effects on central sensitization.…”
Section: Medical Treatment In Painful Cpmentioning
confidence: 99%
“…Gabapentinoid agents including gabapentin and pregabalin work through several different mechanisms, [98–100] but their effect has been promising in terms of ameliorating CP pain both in rat models [80,101] and human clinical studies. Pregabalin has been shown to significantly reduce pain compared to placebo in a randomized controlled trial and has even been shown to have moderate inhibitory effects on central sensitization.…”
Section: Medical Treatment In Painful Cpmentioning
confidence: 99%
“…Therefore, gabapentin was once considered an important drug for the treatment of NP syndromes (58, 59). Available studies have shown that short-term use (three months) could lead to adverse cardiovascular disease (60) while long-term use of gabapentin could damage musculoskeletal conditions (61)(62)(63). Knowing the potential complications can have a considerable impact on the treatment plan given by the clinician.…”
Section: Treatment Of Npmentioning
confidence: 99%